EFEKTIVITAS PEMBEBASAN BERSYARAT TERHADAP NARAPIDANA NARKOTIKA DI LAPAS: ANTARA KEADILAN DAN PEMBINAAN - Henny Saida Flora (Fiat Iustitia : Jurnal Hukum, 2025)
Parole is one of the instruments in the correctional system which aims to provide prisoners with the opportunity to re-adapt to community life. In the context of narcotics crimes, the application of parole often raises debates, especially regarding its effectiveness in achieving justice and guidance. This research aims to analyze the effectiveness of parole for narcotics convicts in correctional institutions, by reviewing juridical, sociological aspects and policy implementation in the field. The research method used is normative-empirical research by examining statutory regulations, legal doctrine, as well as the results of interviews and observations in prisons. The research results show that parole has positive potential in the process of resocialization of narcotics prisoners, but still faces obstacles in the form of high recidivism rates, limited coaching programs, and negative public perceptions. Therefore, the effectiveness of parole will be achieved if it is accompanied by strict supervision, a sustainable rehabilitation program, and support from the community in the social reintegration process. This research recommends strengthening regulations and collaboration between institutions so that correctional goals can run in line with the principles of substantive justice.